Synergistic Effects of Rhizophagus irregularis and Trichoderma harzianum Co-Inoculation on Enhancing Drought Tolerance and Secondary Metabolite Production in Licorice (Glycyrrhiza uralensis) - Kangxu Zhang; Mengyao Sun; Haiyan Feng; Xia Wei; Wei Xie; Wei Fu; Lanping Guo; Xin Zhang; Zhipeng Hao; Baodong Chen (Journal of Fungi)
Drought stress significantly hinders the cultivation of medicinal plants such as licorice (Glycyrrhiza uralensis), valued for its bioactive compounds, glycyrrhizin, and liquiritin. This study aims to investigate how co-inoculation with arbuscular mycorrhizal fungus Rhizophagus irregularis and Trichoderma harzianum can enhance licorice drought tolerance and secondary metabolite production, providing insights for sustainable agriculture in arid regions. The results demonstrate that inoculation with R. irregularis significantly improved biomass, drought stress tolerance, and increased glycyrrhizin and liquiritin concentrations by 29.9% and 3.3-fold, respectively, particularly under drought conditions. Co-inoculation with T. harzianum further boosted glycyrrhizin yield by 93.7%, indicating a synergistic relationship between the two microbes. The expression of key biosynthetic genes, including squalene synthase (SQS1) for glycyrrhizin and chalcone synthase (CHS) for liquiritin, was significantly upregulated, enhancing water use efficiency and the biosynthesis of secondary metabolites. Nutrient analysis showed improved phosphorus uptake, alongside reduced root carbon and nitrogen concentrations, leading to greater nutrient utilization efficiency. These findings suggest that co-inoculating R. irregularis and T. harzianum is a promising approach to improving licorice growth and medicinal quality under drought stress, with broad applications for sustainable crop management.